2018
DOI: 10.21037/jtd.2018.11.40
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lobar lymph node metastasis in non-small cell lung carcinoma using modified total lesion glycolysis

Abstract: Background: Volumetric parameters based on 3-dimensional reconstruction have recently been introduced for cancer staging. We aimed to improve the ability to diagnose hilar lymph node metastasis in patients with non-small cell lung cancer. Methods: We evaluated 142 patients with non-small cell lung cancer who underwent right upper lobectomy and radical lymph node dissection. Metastatic involvement of right upper lobar lymph nodes was assessed using high-resolution computed tomography (HRCT) and 18F-2-floro-2-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Some lymph node metastases, such as micrometastases, do not give an accurate metastasis evaluation no matter how closely the degree of swelling of the lymph nodes, area under an ROC curve; C/T: CD/T; CD: maximal consolidation diameter evaluated with lung window setting; T: total tumor diameter evaluated with lung window setting; LN: lymph node metastasis; ly: lymph vessel invasion; MD: maximal diameter evaluated with mediastinal window setting; pl: pleural invasion; ROC: receiver operating characteristic; SUVmax: maximum standardized uptake value; v: vascular invasion or the uptake of FDG into the lymph nodes, are examined. [17][18][19] We have reported that both the imaging findings (MD, solid components of tumor) of the tumor and CEA values are highly correlated with the degree of tumor invasiveness, which allows more accurate preoperative evaluation of lymph node metastasis in cIA. [5][6][7][8]20) CD is a rational tumor size measurement method that reflects the degree of adenocarcinoma, and was adopted in the 8th edition WHO classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some lymph node metastases, such as micrometastases, do not give an accurate metastasis evaluation no matter how closely the degree of swelling of the lymph nodes, area under an ROC curve; C/T: CD/T; CD: maximal consolidation diameter evaluated with lung window setting; T: total tumor diameter evaluated with lung window setting; LN: lymph node metastasis; ly: lymph vessel invasion; MD: maximal diameter evaluated with mediastinal window setting; pl: pleural invasion; ROC: receiver operating characteristic; SUVmax: maximum standardized uptake value; v: vascular invasion or the uptake of FDG into the lymph nodes, are examined. [17][18][19] We have reported that both the imaging findings (MD, solid components of tumor) of the tumor and CEA values are highly correlated with the degree of tumor invasiveness, which allows more accurate preoperative evaluation of lymph node metastasis in cIA. [5][6][7][8]20) CD is a rational tumor size measurement method that reflects the degree of adenocarcinoma, and was adopted in the 8th edition WHO classification.…”
Section: Discussionmentioning
confidence: 99%
“…Some lymph node metastases, such as micrometastases, do not give an accurate metastasis evaluation no matter how closely the degree of swelling of the lymph nodes, or the uptake of FDG into the lymph nodes, are examined. 17 19) We have reported that both the imaging findings (MD, solid components of tumor) of the tumor and CEA values are highly correlated with the degree of tumor invasiveness, which allows more accurate preoperative evaluation of lymph node metastasis in cIA. 5 8 , 20) CD is a rational tumor size measurement method that reflects the degree of adenocarcinoma, and was adopted in the 8th edition WHO classification.…”
Section: Discussionmentioning
confidence: 99%
“…All patients underwent 18 FDG-PET prior to surgical resection. The generation and evaluation of 18 FDG-PET scans has been described in detail in previously published articles [19][20][21][22]. PET-CT images were acquired according to a standard imaging protocol using a dedicated PET/CT scanner (Biograph 40; SIEMENS Healthcare Japan Co., Japan).…”
Section: Pet-ct Acquisition and Distributionmentioning
confidence: 99%
“…Parameters such as total lung glycolysis (TLG), as well as maximum and mean 18 F-FDG uptake, were obtained by PET, whereas TLG was calculated as the product of mean 18 F-FDG uptake and metabolic tumour volume. The maximum and mean 18 F-FDG uptake and the metabolic tumour volume of NSCLC and ILD areas were calculated using a SIEMENS MMWP workstation, as previously reported [19][20][21][22]. A technical assistant blinded to the clinical data calculated these parameters.…”
Section: Pet-ct Acquisition and Distributionmentioning
confidence: 99%